Revitalisasi Pendidikan Aceh - M. Shabri A. Majid (Jurnal Pencerahan, 2016)
The system of education plays a significant role in all aspects of human life, including in empowering the welfare of its citizens. A good system of education during the Kingdom of Aceh Darussalam has led her people to be saluted and admired both by locals and foreigners. This study aims at discovering the problem hampering the system of education, focusing on the district of Aceh as a case study as well as providing the recommendation for enhancing its educational system. To establish a good educational system, we need to reform the curricula, renovate the educational facilities, empower lecturers’ abilities and skills, improve students’ quality, and shorten educational bureaucracy. To produce a knowledgeable and taqwa (pious) student, the curricula of Islamic educational system have to be in harmony with the Divine injunctions, al-Qur’an and Hadits. Then, the educational facilities, lecturers’ abilities, and skills of teaching and educational bureaucracy as well have to enhance and monitored regularly for from time to time. The experiences of success from other countries and universities in their adoption of Islamic educational system, such as International Islamic University Malaysia (IIUM) can be comprehensively learned as the basis for the future educational reforms. Finally, to make good educational system be realized, the government has also to actively cooperate and involve in empowering the educational system, inter alia, by providing sufficient budget for educational agenda.